Obstetricians/Gynecologists' Problems in Sickness Certification Consultations: Two Nationwide Surveys. (17th November 2016) - Gustavsson, Catharina; Hinas, Elin; Ljungquist, Therese; Alexanderson, Kristina
Abstract : Objective. To explore experiences by physicians working in obstetrics, gynecology, or maternal healthcare (O/Gs) of problems in sickness certification consultations and differences between two years. Material and Methods. Answers by O/Gs to two Swedish nationwide surveys, in 2008 (n = 1037 ) and 2012 (n = 992 ), were analyzed for frequencies and severity of problems and organizational support in sickness certification consultations. Results. One-third of O/Gs found sickness certifications problematic every week. The most frequent problem was patients requesting sick notes for reasons other than work incapacity due to disease/injury (2008: 21%; 2012: 16%). The most problematic were assessing work capacity (2008 and 2012: 52%) and having different opinion from that of the patient about need for sick leave (2008: 51%; 2012: 46%). In 2012, 27% used the national sickness certification guidelines weekly, compared to 9% in 2008. A larger proportion in 2012 than 2008 reported that the guidelines facilitated contacts with patients and different stakeholders. Conclusions. Although O/Gs perceived sickness certification as problematic, there was less perceived severity of problems in 2012 compared to 2008, possibly because interventions regarding sickness certification have been introduced in Sweden recent years. Still, more organizational support, for example, time and supervision, are needed to enhance O/Gs' sickness certification practices.